EARLY MOBILIZATION BEHAVIOR OF MOTHER POST SECTION CAESAREA AT EMBUNG FATIMAH HOSPITAL BATAM CITY - susanti susanti; Ika Novita Sari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Early mobilization is a prominent factor in accelerating post-section cesarean recovery and can prevent post-section cesarean complications. The principle of early mobilization in post section Caesarea is carried out gradually and regularly followed by rest and adjusted to the client's physical condition. The purpose of this study was to determine the attitudes with early mobilization behavior in post-section Caesarea mothers in the combined obstetrics ward at RSUD Embung Fatimah Batam City. The research method used descriptive research with a quantitative approach. The research design used cross-sectional. The sample in the study amounted to 50 people from the entire population of post-section Caesarea mothers who were treated in the combined obstetrics ward of RSUD Embung Fatimah Batam City. The sampling technique was accidental sampling. The research instrument uses a questionnaire that has been tested for validity and reliability. The results showed that from 50 respondents with good knowledge, 34 respondents (68%) with good early mobilization behavior, and 16 respondents (32%) with poor early mobilization behavior. This shows the importance of the mother's ability to carry out early mobilization of post-sectio caesarea mothers to improve more effective recovery in post-sectio caesarea conditions. Keywords : Early Mobilization; Behavior, Post Sectio Caesarea